Mengatasi pola perilaku pra remaja pasca covid 19 dari sudut pandang pendidikan agama Islam - Sukatin Sukatin; Sorta Maharani. S; Siti Izzatul Mabruroh; Wahyuni Wahyuni; Fernando Ibrahim (ARKA INSTITUTE, 2022)
After covid 19, The educational institutions began to switch status from online to offline in accordance with applicable government policies. According to the results of the research found by researchers, pre-adolescent behavior patterns experienced a significant increase which was usually difficult to manage to become increasingly difficult to regulate until it was out of control. The way the teacher overcomes this problem is by instilling the value of Islamic religious education in the form of religious, intellectual, moral, psychological, and social values. The findings made by researchers show that educators instill these values so that the behavior patterns of pre-adolescent gradually change. This research used a qualitative descriptive method with a case study approach. This research collected the data by structured interview method and took samples by using the convenience sampling technique.